"Clean out of the map": Knowing and doubting space at India's high imperial frontiers. (March 2017) - Simpson, Thomas
During the second half of the nineteenth century, land frontiers became areas of unique significance for surveyors in colonial India. These regions were understood to provide the most stringent tests for the men, instruments, and techniques that collectively constituted spatial data and representations. In many instances, however, the severity of the challenges that India's frontiers afforded stretched practices in the field and in the survey office beyond breaking point. Far from producing supposedly unequivocal maps, many involved in frontier surveying acknowledged that their work was problematic, partial, and prone to contrary readings. They increasingly came to construe frontiers as spaces that exceeded scientific understanding, and resorted to descriptions that emphasized fantastical and disorienting embodied experiences. Through examining the many crises and multiple agents of frontier mapping in British India, this article argues that colonial surveying and its outputs were less assured and more convoluted than previous histories have acknowledged.